Rocks & Minerals - Symes, R. F. Dr. (New York Alfred A. Knope)
Examines the creation, importance, erosion, mining, and uses of rocks and minerals
Include Color Illustration and Index
Keywords: Rocks -- Juvenile literature -- Mineralogy -- Juvenile literature